ESTUDO DA FOTODEGRADAÇÃO DO CORANTE AZO-RB-5 ATRAVÉS DO USO DE HDL DE M2+/Cr3+ (M2+ = Mg, Zn, Cu, Ni) - Oliveira, Kaio Vinicius Bernardo de (2017)
Of the classes of synthetic dyes used by the textile industry, those of azo type are used in large quantities, because they have excellent dyeing qualities. One of the typical dyes of this class (and used as its representative in this work) is Reactive Black 5 (RB-5), which is usually applied in the dyeing process in the finishing stage. Of the methods used for discoloration of textile effluents, photocatalysis is highlighted because it is relatively inexpensive, efficient and demineralizes the dye in non-harmful, environmentally-friendly molecules. One of the ways to carry out photocatalytic reactions is the one that uses semiconductor materials and source of UV-Vis radiation, to promote redox reactions. One of the currently widely studied semiconductor materials, and of several applications, is Layered Double Hydroxides (LDHs). In several reaction systems designed for industrial application, experimental design is useful to improve the response(s) by studying the variables of interest present in the system, which results in improved yields and savings. In this work, the Central Composite Design Rotable (CCDR) technique was applied for experimental design, which consists of three different types of experiments: factorial, axial and central. Were evaluated the effects and interactions of temperature, catalyst concentration and dye concentration on RB-5 dye demineralization. Cr3+ and M2+ HDLs (M = Mg, Zn, Ni and Cu) are synthesized in the ratio 2:1, respectively, with NO3- as an intercalated anion. HDLs were obtained by the coprecipitation method at constant pH and were characterized by DRX, TGA-DTA, Zeta Potential and UV-Vis. The HDLs synthesized presented ratio: Cu3Cr; Zn2Cr; Mg1,07Cr; Ni2,5Cr. They responded relatively well to the demineralization of the RB-5, for the first use of the material: CuCr(96,84%); ZnCr(91,34%); MgCr(93,55%) e NiCr(79,06%). During the following uses, there was a decrease of the effectiveness of the materials, being carried out the efficiency monitoring until the sixth use of the catalysts. CuCr (96,84; 73,72; 63,90; 53,82; 25,03; 25,89 %); ZnCr (91,34; 95,59; 88,22; 68,40; 42,69; 32,56 %); MgCr (93,55; 65,27; 44,56; 24,73; 24,19; 11,65 %) e NiCr (79,06; 94,23; 76,22; 35,60; 24,99 %).